Positive electrode active material, positive electrode comprising the positive electrode active material, and rechargeable lithium battery comprising the positive electrode active material
Patent Information
- Application Number
- CN202610525986.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-24
- Filing Date
- 2026-04-21
- Publication Date
- 2026-10-27
AI Technical Summary
但是存在以下问题:在压缩工艺期间引起在极板中的活性物质中的破裂(裂纹),这损害电化学特性
Smart Images

Figure CN122992011A_ABST
Abstract
Description
Technical Field
[0001] A positive electrode active material, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode active material are disclosed. Background Technology
[0002] Portable information devices such as cellular phones, laptops, and smartphones use rechargeable lithium batteries with high energy density and portability. Research has been actively conducted on using high-energy-density rechargeable lithium batteries as a power source or energy storage source for hybrid or electric vehicles.
[0003] Such rechargeable lithium batteries require high electrode density. To achieve high electrode density, a compression process is performed during the manufacture of the electrode plates. However, this compression process causes cracking in the active material within the electrode plates, which impairs electrochemical properties. Summary of the Invention
[0004] A positive electrode active material capable of improving particle strength while mitigating breakage in the active material during compression is provided, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode active material.
[0005] In some example embodiments, a positive electrode active material is provided, comprising: a core particle comprising a lithium transition metal composite oxide and in the form of a secondary particle formed by the agglomeration of primary particles; and a carbon coating layer on the surface of the core particle, wherein the positive electrode active material has a particle strength greater than or equal to about 160 MPa.
[0006] In some example implementations, a positive electrode is provided, which includes a current collector and a layer of positive electrode active material disposed on the current collector and including the positive electrode active material.
[0007] In some example implementations, a rechargeable lithium battery is provided, comprising: the positive electrode; the negative electrode; and an electrolyte.
[0008] According to some example embodiments, the positive electrode active material has improved particle strength and particle surface lubricity, and can prevent cracking during compression.
[0009] Because the positive electrode according to the embodiment includes the positive electrode active material, the density of the electrode plate can be improved and the number of pores in the electrode plate can be reduced.
[0010] The rechargeable lithium battery according to the embodiment can improve capacity and energy density and has a long cycle life because it includes the positive electrode active material. Attached Figure Description
[0011] Figures 1 to 4 A diagram of a rechargeable lithium battery according to an embodiment.
[0012] Figure 5 This is a scanning electron microscope image of the positive electrode active material prepared in Example 1.
[0013] Figure 6 This is a scanning electron microscope image of the positive electrode active material prepared in Comparative Example 3.
[0014] Figure 7 This is a scanning electron microscope image of the positive electrode active material prepared in Comparative Example 4.
[0015] Figure 8 This is a scanning electron microscope image of the cross-section of the positive electrode fabricated in Example 1.
[0016] Figure 9 This is a scanning electron microscope image of the cross-section of the positive electrode fabricated in Example 2.
[0017] Figure 10 This is a scanning electron microscope image of the cross-section of the positive electrode fabricated in Comparative Example 1.
[0018] Figure 11 This is a scanning electron microscope image of the cross-section of the positive electrode fabricated in Comparative Example 2.
[0019] Figure 12 This is a scanning electron microscope image of the cross-section of the positive electrode fabricated in Comparative Example 3.
[0020] Figure 13 This is a scanning electron microscope image of the cross-section of the positive electrode fabricated in Comparative Example 4. Detailed Implementation
[0021] Specific implementation methods will be described in detail below so that those skilled in the art can readily implement them. However, this disclosure may be embodied in many different forms and is not limited to the exemplary implementation methods set forth herein.
[0022] The terminology used herein is for descriptive purposes only and is not intended to limit the scope of this disclosure. Unless the context clearly requires otherwise, singular expressions include plural expressions.
[0023] "The combination of its components" means mixtures, laminates, complexes, copolymers, alloys, blends, reaction products, etc.
[0024] It should be understood that terms such as “comprising,” “including,” or “having” are intended to indicate the presence of the features, quantities, steps, elements, or combinations thereof embodied, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0025] In the accompanying drawings, for clarity, the thickness of layers, films, panels, regions, etc., is exaggerated, and the same reference numerals denote the same elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on said other element, or there may be intermediate elements present. In contrast, when an element is referred to as being "directly on" another element, there are no intermediate elements.
[0026] The term "layer" in this article includes not only the shape that forms on the entire surface when viewed from a plan view, but also the shape that forms on a portion of the surface.
[0027] The average particle size can be measured using methods well known to those skilled in the art, such as by a particle size analyzer or by transmission electron microscopy or scanning electron microscopy images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles in each particle size range, and calculating therefrom. Unless otherwise defined, the average particle size can mean the diameter (D) of particles having a cumulative volume of 50% in the particle size distribution. 50 As used herein, unless otherwise defined, mean particle size means the diameter of the particles representing 50% of the cumulative volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of approximately 20 particles in a scanning electron microscope image. 50 ).
[0028] In this article, "or" is not interpreted as having an exclusive meaning. For example, "A or B" is interpreted as including A, B, A+B, etc.
[0029] The term "metal" is interpreted as encompassing common metals, transition metals, and metalloids (semi-metals).
[0030] Positive electrode active material
[0031] The positive electrode active material according to the embodiment includes core particles, which are lithium transition metal composite oxides and are in the form of secondary particles formed by the aggregation of multiple primary particles. The positive electrode active material includes a carbon coating layer on the surface of the core particles. Furthermore, the positive electrode active material has a particle strength greater than or equal to about 160 MPa.
[0032] Typically, the following drawback exists: reduced electronic or ionic conductivity due to pores within the positive electrode. To address this issue and achieve high electrode plate density, a compression process is performed during the manufacturing of the positive electrode. However, this process introduces the problem of cracking within the positive electrode active material. Particularly in the case of positive electrode active materials formed from the aggregation of multiple primary particles into secondary particles, the cracking is more severe during compression due to the weak particle strength.
[0033] According to some embodiments, the positive electrode active material has a high particle strength of about 160 MPa or greater because it comprises a core particle and a carbon coating layer on the surface of the core particle. Therefore, breakage in the active material that occurs during compression of the positive electrode can be mitigated, and compression processes can be performed at higher pressures.
[0034] Furthermore, because the positive electrode active material has high surface lubricity, it also exhibits a sliding effect, even when there is contact between the positive electrode active materials, external pressure, or external force. Therefore, even when compressed under high pressure during the manufacturing of the positive electrode, the impact applied to the active material is buffered, and the compression efficiency of the positive electrode is improved.
[0035] Therefore, because the positive electrode active material has high particle strength and surface lubricity, it can undergo compression processing under high pressure while protecting the active material from the effects of the compression process. Consequently, the positive electrode including the positive electrode active material can have reduced porosity and further improve the mixing density (mixture density) of the positive electrode. Furthermore, the rechargeable lithium battery can have improved capacity and energy density, and can have a long cycle life because degradation is delayed.
[0036] The preparation of the positive electrode active material according to some embodiments is described in detail below.
[0037] Core Particles
[0038] The core particles comprise lithium transition metal composite oxides and are in the form of secondary particles formed by the aggregation of multiple primary particles.
[0039] The lithium transition metal composite oxide of the core particles may include lithium nickel-based oxides, lithium cobalt-based oxides, lithium manganese-based oxides, lithium iron phosphate (lithium iron phosphate)-based compounds, cobalt-free lithium nickel manganese-based oxides, lithium manganese-rich composite oxides, or combinations thereof.
[0040] For example, the lithium transition metal complex oxide of the core particle can be a compound represented by any of the following chemical formulas: Li a A 1-b X b O2-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Mn 2-b X b About 4-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Ni 1-b-c Co b X c About 2-α D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b-c Mn b X c About 2-α D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0≤e≤0.1);Li a NiG b O2 (0.90≤a≤1.8,0.001≤b≤0.1);Li a CoG b O2 (0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn 1-b G b O2 (0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn2G b O4 (0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn 1-g G g PO4 (0.90≤a≤1.8,0≤g≤0.5);Li (3-f) Fe2(PO4)3 (0≤f≤2);Li aFePO4 (0.90≤a≤1.8). In these chemical formulae, A is Ni, Co, Mn or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; and L 1 is Mn, Al or a combination thereof.
[0041] In some examples, the lithium transition metal composite oxide of the core particles may include a lithium nickel-based composite oxide represented by the following Chemical Formula 1, a lithium cobalt-based oxide represented by the following Chemical Formula 2, a lithium iron phosphate-based compound represented by the following Chemical Formula 3, a cobalt-free lithium nickel manganese-based oxide represented by the following Chemical Formula 4, or a combination thereof.
[0042] [Chemical Formula 1]
[0043] Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1
[0044] In Chemical Formula 1, 0.9≤a1≤1.2, 0.3≤x1<1, 0<y1≤0.7, 0≤z1≤0.7, 0.9≤x1+y1+z1≤1.1, and 0≤b1≤0.1, M 1 and M 2 are each independently one or more elements selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, Y, W and Zr, and X is one or more selected from F, P and S.
[0045] [Chemical Formula 2]
[0046] Li a2 Co x2 M 3 y2 O 2-b2 X b2
[0047] In Chemical Formula 2, 0.9≤a2≤1.8, 0.7≤x2≤1, 0≤y2≤0.3, 0.9≤x2+y2≤1.1, and 0≤b2≤0.1, M 3 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn and Zr, and X is one or more selected from F, P and S.
[0048] [Chemical Formula 3]
[0049] Li a3 Fe x3 M 4 y3 PO 4-b3 X b3
[0050] In Chemical Formula 3, 0.9≤a3≤1.8, 0.6≤x3≤1, 0≤y3≤0.4, and 0≤b3≤0.1, M 4 is one or more elements selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn and Zr, and X is one or more selected from F, P and S.
[0051] [Chemical Formula 4]
[0052] Li a4 Ni x4 Mn y4 M 5 z4 O 2-b4 X b4
[0053] In Chemical Formula 4, 0.9≤a4≤1.8, 0.8≤x4<1, 0<y4≤0.2, 0≤z4≤0.2, 0.9≤x4+y4+z4≤1.1, and 0≤b4≤0.1, M 5 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y and Zr, and X is one or more selected from F, P and S.
[0054] When the lithium transition metal composite oxide of the core particles may include the lithium nickel-based composite oxide represented by Chemical Formula 1, a rechargeable lithium battery with high capacity and high energy density can be realized.
[0055] In some examples, the lithium transition metal composite oxide of the core particles may include a compound represented by Chemical Formula 5 or Chemical Formula 6.
[0056] [Chemical Formula 5]
[0057] Li a5 Ni x5 Co y5 M 6 z5 O 2-b5 X b5
[0058] In Chemical Formula 5, 0.9≤a5≤1.2, 0.8≤x5<1, 0<y5≤0.2, 0≤z5≤0.2, 0.9≤x5+y5+z5≤1.1, and 0≤b5≤0.1, M 6 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X is one or more selected from F, P, and S.
[0059] In Chemical Formula 5, 0.9≤x5≤0.99, 0.01≤y5≤0.1, and 0≤z5≤0.1.
[0060] [Chemical Formula 6]
[0061] Li a6 Ni x6 Co y6 M 7 z6 M 8 w6 O 2-b6 X b6
[0062] In Chemical Formula 6, 0.9≤a6≤1.2, 0.8≤x6≤0.98, 0.01≤y6≤0.19, 0.01≤z6≤0.19, 0≤w6≤0.19, 0.9≤x6+y6+z6+w6≤1.1, and 0≤b6≤0.1, M 7 is one or more elements selected from Al, Mn, or a combination thereof, M 8 is one or more selected from B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, M 7 and M 8 are different from each other, and X is one or more elements selected from F, P, and S. In a further embodiment of Chemical Formula 6, 0.9≤x6≤0.98, 0.01≤y6≤0.09, 0.01≤z6≤0.09, and 0≤w6≤0.09.
[0063] Nickel may be included in the lithium transition metal composite oxide of the core particles in an amount of greater than or equal to about 80 mol%, for example, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%, based on 100 mol% of the total metals excluding lithium. In this case, the core particles may be a high-nickel positive electrode active material. Since the high-nickel positive electrode active material can achieve high capacity, high capacity and high density in a rechargeable lithium battery can be realized in such an embodiment.
[0064] Core particles are secondary particles formed by tightly agglomerating (attaching) primary particles. Secondary particles can be spherical, ellipsoidal, polyhedral, or irregular in shape, and the primary particles forming the secondary particles can be spherical, ellipsoidal, plate-shaped, or a combination thereof.
[0065] The average particle size (D) of the secondary particles in the core particles 50 The primary particle size (D) of the secondary particles can be from about 6 μm to about 25 μm, for example, from about 6 μm to about 23 μm, from about 7 μm to about 20 μm, or from about 8 μm to about 15 μm. 50 The size of the secondary particles can be from about 10 nm to about 1 μm, for example, from about 10 nm to about 800 nm, from about 20 nm to about 500 nm, or from about 50 nm to about 200 nm. Here, the average particle size (D) of the secondary particles is... 50 The particle size distribution can be obtained as follows: Approximately 20 particles are randomly selected from the scanning electron microscope images of the secondary particles, and their particle sizes (diameter, major axis, or major axis length) are measured to obtain the particle size distribution. The size of the particles representing 50% of the cumulative volume from this distribution is then taken as the average particle size. The average particle size (D) of the primary particles forming the secondary particles is... 50 The average particle size can be obtained by measuring the size of approximately 30 primary particles in an electron microscope image of the surface or cross-section of the secondary particles, and taking the diameter of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0066] The porosity of secondary particles can be from about 2% to about 20%. Here, porosity is the ratio of the area occupied by pores within the particle, measured using an image analysis program such as ImageJ in a scanning electron microscope image of the cross-section of the secondary particle.
[0067] carbon coating
[0068] The carbon coating is applied to the surface of the core particles and improves the particle strength and surface lubrication of the positive electrode active material. Therefore, it reduces breakage in the positive electrode active material (which would otherwise occur during compression of the positive electrode) and allows for compression processes at higher pressures.
[0069] Thanks to the carbon coating, even with minimal use of binders and conductive materials in the manufacturing of the positive electrode, strong adhesion and conductivity to the electrode plate are ensured. As the amount of binder or conductive material decreases, the amount of active material in the positive electrode can increase, enabling rechargeable lithium batteries to exhibit high capacity and high energy density characteristics.
[0070] The carbon coating may include graphene with a layered structure of 50 layers or fewer. Techniques have been proposed to coat the surface of particles with amorphous carbon for use as positive electrode active materials; however, uniform coating is difficult and there are limitations on the particle strength and surface lubricity of the active material. According to embodiments of this disclosure, because the positive electrode active material comprises a carbon coating including crystalline carbon formed in a two-dimensional plane, and the carbon coating is formed in a uniform film shape with a thickness of several nanometers to tens of nanometers, a higher mixing density of the electrode plate can be achieved compared to the case where amorphous carbon is provided. Therefore, the electronic and ionic conductivity of the positive electrode can be improved, energy density can be increased while reducing resistance, and better electrochemical performance can be achieved.
[0071] A layered structure with 50 or fewer layers can be represented as a layered structure with 50 atomic layers or fewer. For example, a carbon coating layer may include graphene with a layered structure having 2 to 50 layers, 2 to 48 layers, 5 to 45 layers, 7 to 40 layers, or 10 to 35 layers. The number of layers in the layered structure can be measured by high-resolution transmission electron microscopy (HR-TEM) images of the positive electrode active material particles.
[0072] The interlayer spacing (d) of the layered structure 002 The interlayer spacing (d) can be from about 0.320 nm to about 0.350 nm, for example, from about 0.325 nm to about 0.348 nm, from about 0.328 nm to about 0.345 nm, or from about 0.330 nm to about 0.342 nm. 002 Within these ranges, the particle strength and surface lubrication of the positive electrode active material can be improved, and the density of the positive electrode active material layer can be maximized. Here, the interlayer spacing (d) 002 ) can be measured using methods known to those skilled in the art. For example, the interlayer spacing (d) of a layered structure 002 The peaks on the (002) plane can be obtained by X-ray diffraction (XRD) of the carbon-coated layer, and then analyzed. Here, the (002) plane represents the range of 25.0° < 2θ < 27.0°, where 2θ represents the diffraction angle. For example, conventional procedures equipped in the XRD apparatus can be used as data processing and analysis procedures to subject the XRD measurement data to noise removal (baseline setting), etc. In addition, the peak profiles on the (002) plane can be fitted using conventional fitting functions such as Gaussian functions, Lorentz functions, etc. In addition, the interlayer spacing (d) of the layered structure 002 This can be achieved by measuring the interlayer spacing (d) of plate-shaped carbon materials. 002 The method is used to represent the interlayer spacing (d) of the plate-like carbon material. 002 The number of layers and the interlayer spacing (d) in a layered structure can be measured via XRD analysis of plate-like carbon materials. 002The thickness of the coating layer was determined as an average of measurements of the cross-section of the core particle at multiple randomly selected locations using HR-TEM. Note that the correlation between these parameters follows the physical properties of the graphene coating layer, where the total thickness of the coating layer is the product of the number of layers and the average interlayer spacing.
[0073] In the carbon coating layer, graphene can be derived from plate-like carbon materials. Plate-like carbon materials can be represented as sheet-like carbon materials or 2D carbon materials, and can include, for example, crystalline carbon. For example, plate-like carbon materials can include graphene, graphite, or combinations thereof, and can be, for example, particulate graphite. The graphene in the carbon coating layer can be derived from particulate graphite. In such embodiments, the carbon coating layer has a layered structure exhibiting a dense crystalline structure, including crystalline carbon formed in a two-dimensional plane on the surface of the core particles, and can have a thin and uniform thickness. Therefore, the particle strength and surface lubricity of the positive electrode active material can be further improved. In addition, the mixing density, electronic conductivity, and interfacial resistance of the positive electrode can be improved, lithium ion insertion and deintercalation can be more efficient, and ionic conductivity can be improved because lithium ions can diffuse along the layered structure.
[0074] The average size (D) of plate-shaped carbon materials 50 The average size of the plate-like carbon material can be less than or equal to about 2.5 μm, for example, less than or equal to about 1.5 μm, less than or equal to about 1.0 μm, less than 1 μm, less than or equal to about 0.5 μm, greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm, and can be about 10 nm to about 1,000 nm, about 30 nm to about 950 nm, or about 50 nm to about 900 nm. When the average size of the plate-like carbon material is within these ranges, a carbon coating layer of uniform thickness can be formed on the surface of the core particles, and the particle strength and surface lubricity of the positive electrode active material can be maximized. Here, the average size of the plate-like carbon material (D...) 50 The particle size can be measured using a particle size analyzer, and the average size (D) 50 ) refers to the size of particles that have a cumulative volume of 50% in the particle size distribution. Furthermore, particle size here can mean the length of the longest axis in a plane perpendicular to the thickness direction in a plate shape.
[0075] The thickness of the plate-like carbon material can be less than or equal to about 1.0 μm, for example, less than or equal to about 1 μm, less than or equal to about 0.9 μm, less than or equal to about 0.7 μm, or less than or equal to about 0.5 μm, greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm, and can be about 5 nm to about 500 nm, about 5 nm to about 300 nm, or about 5 nm to about 100 nm. When the thickness of the plate-like carbon material is within these ranges, a carbon coating layer of uniform thickness can be formed on the surface of the secondary particles, and the particle strength, particle surface lubrication, and density of the positive electrode active material layer can be maximized. Here, the thickness of the plate-like carbon material can be measured by scanning electron microscopy (SEM) or transmission electron microscopy (TEM) images of the plate-like carbon material particles.
[0076] The plate-like carbon material may have a ratio of the length of its long axis in the planar direction to its thickness of 2 to 1000, for example 2 to 800, 2 to 500, or 2 to 50. When the ratio of the length of the long axis in the planar direction to its thickness of the plate-like carbon material is within these ranges, a carbon coating layer of uniform thickness can be formed on the surface of the core particles, and the particle strength and surface lubricity of the positive electrode active material can be maximized. Here, the ratio of the length of the long axis in the planar direction to its thickness can be measured based on electron microscopy images. For example, from an SEM image of the plate-like carbon material, the thickness of the plate-like carbon material can be measured, and the length of the longest axis in the planar direction orthogonal to (perpendicular to) the thickness direction can be measured to calculate the ratio. The thickness and long axis length of the plate-like carbon material may mean the arithmetic mean of the values obtained through image analysis of multiple plate-like carbon materials.
[0077] The plate-shaped carbon material may have a Raman spectral density of about 0.05 to about 0.50, for example about 0.05 to about 0.45, about 0.10 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G When the plate-shaped carbon material I D / I G When the values are within these ranges, a carbon coating layer of uniform thickness can be formed on the surface of the core particles, maximizing the particle strength and surface lubricity of the positive electrode active material. For example, a Raman spectrometer (e.g., ICRM7000 (Renishaw)) can be used at a laser wavelength of approximately 632 nm and a wavelength of approximately 946 cm⁻¹. -1The Raman spectra were measured under the condition of the lowest Raman shift. The peak intensity ratios described in this paper are derived from the values at approximately 946 cm⁻¹. -1 The peaks observed were obtained from the Raman shift range starting from the lowest Raman shift. These measurement conditions are standard in the art and the following are within the capabilities of those skilled in the art: adjusting these parameters, such as laser power or exposure time, while maintaining the relative trend of the peak intensity ratio to ensure reproducibility.
[0078] Based on a total of 100 wt% of the positive electrode active material layer, a carbon coating layer may be included in amounts from about 0.05 wt% to about 5.0 wt%, for example, from about 0.1 wt% to about 5.0 wt%, from about 0.2 wt% to about 5.0 wt%, from about 0.2 wt% to about 3.0 wt%, from about 0.2 wt% to about 2.5 wt%, from about 0.2 wt% to about 2.0 wt%, from about 0.2 wt% to about 1.0 wt%, or from about 0.2 wt% to about 0.8 wt%. When the amount of the carbon coating layer is within these ranges, the particle strength and surface lubricity of the positive electrode active material can be improved. Even if the amount of the carbon coating layer is less than about 1 wt%, carbon can still be well coated on the surface of the core particles, thereby increasing the electrical conductivity of the positive electrode active material, increasing lubricity, and increasing the density of the positive electrode. If the carbon coating layer includes graphene having a layered structure of 50 layers or less, the amount of graphene can be described as being the same as the amount of the carbon coating layer.
[0079] The carbon coating can be in the form of a continuous film or islands (i.e., discontinuous islands). For example, the carbon coating can be in the form of a film that continuously surrounds the surface of the core particle. In other examples, the carbon coating can be in the form of a shell that surrounds the entire surface of the core particle. When the carbon coating is formed to completely cover the surface of the core particle, the particle strength and surface lubricity of the positive electrode active material can be improved. Furthermore, the positive electrode active material can have improved structural stability without increasing resistance or reducing capacity, and the density of the positive electrode active material layer including the positive electrode active material can be improved.
[0080] The carbon coating may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G When the carbon coating layer I D / I GWhen the values are within these ranges, the degradation of the positive electrode active material can be reduced, the particle strength of the positive electrode active material can be improved, and the density of the positive electrode can be maximized. When the carbon coating layer includes graphene with a layered structure of 50 layers or less, the Ig of graphene... D / I G It can be combined with the carbon coating layer I D / I G Described in the same way.
[0081] The thickness of the carbon coating can be from about 2 nm to about 500 nm, for example, from about 2 nm to about 400 nm, from about 2 nm to about 300 nm, from about 3 nm to about 200 nm, from about 3 nm to about 100 nm, from about 4 nm to about 50 nm, from about 5 nm to about 30 nm, from about 5 nm to about 20 nm, or from about 5 nm to about 15 nm. When the thickness of the carbon coating is within these ranges, the structural stability of the positive electrode active material can be improved without increasing the resistance or reducing the capacity due to the carbon coating. For example, the thickness of the carbon coating can be measured by cross-section of the positive electrode active material particles cut by focused ion beam (FIB) or by TEM of the positive electrode active material particles. However, this disclosure is not limited to such examples, and the thickness of the carbon coating can be measured by, for example, SEM, time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), or energy-dispersive X-ray spectroscopy (EDS), and can be measured by TEM-EDS line profile.
[0082] The difference between the highest and lowest thicknesses of the carbon coating layer in the positive electrode active material particles can be less than or equal to about 30 nm, for example, less than or equal to about 25 nm, less than or equal to about 20 nm, or less than or equal to about 15 nm, greater than or equal to about 0.30 nm, greater than or equal to about 0.33 nm, greater than or equal to about 0.35 nm, or greater than or equal to about 0.40 nm. The difference between the highest and lowest thicknesses of the carbon coating layer within these ranges indicates that a carbon coating layer of uniform thickness is well formed in the form of a film on the surface of the positive electrode active material particles. Therefore, the particle strength and surface lubricity of the positive electrode active material can be further improved. Here, the highest and lowest thicknesses of the carbon coating layer can be measured based on electron microscopy images of the positive electrode active material. For example, in an electron microscopy image of a cross-section of the positive electrode active material particles, the thickness of the thickest portion of the cross-section of the carbon coating layer can be defined as the highest thickness of the carbon coating layer, and the thickness of the thinnest portion can be defined as the lowest thickness of the carbon coating layer. The thickness of the carbon coating can be the vertical distance from the outer surface of the core particle to the outer surface of the carbon coating. SEM or TEM can be used as an electron microscope.
[0083] The positive electrode active material may further include a carbon coating layer on the surface of the primary particles of the core particle. In this case, the carbon coating layer on the surface of the core particle may be referred to as a first carbon coating layer, and the carbon coating layer on the surface of the primary particles may be referred to as a second carbon coating layer.
[0084] The second carbon coating on the surface of the primary particles can further improve the particle strength and surface lubricity of the positive electrode active material. Therefore, cracking in the positive electrode active material (which would otherwise occur during compression of the positive electrode) can be reduced, and compression processes can be performed at higher pressures. Here, the second carbon coating on the surface of the primary particles can be described in the same manner as the first carbon coating on the surface of the core particles described above.
[0085] The average particle size (D) of the positive electrode active material 50 The average particle size (D) of the positive electrode active material can be from about 6 μm to about 25 μm, and can be, for example, from about 9 μm to about 20 μm, from about 10 μm to about 18 μm, or from about 12 μm to about 16 μm. 50 Within these ranges, capacity, energy density, and long cycle life characteristics can be maximized. Here, the average particle size (D) of the positive electrode active material... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from the SEM image of the positive electrode active material, measuring their particle size (diameter, major axis or major axis length) to obtain the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0086] The particle strength of the positive electrode active material can be greater than or equal to about 160 MPa, for example greater than or equal to about 161 MPa, greater than or equal to about 162 MPa, greater than or equal to about 163 MPa, less than or equal to about 300 MPa, less than or equal to about 250 MPa, less than or equal to about 200 MPa, or less than or equal to about 190 MPa, and can be about 160 MPa to about 300 MPa, about 160 MPa to about 245 MPa, or about 160 MPa to about 190 MPa. When the particle strength of the positive electrode active material is within these ranges, less breakage can occur in the particles and the density of the positive electrode active material layer can be improved. Here, the particle strength of the positive electrode active material can be measured by placing the active material particles on a plate, applying compressive force using a particle strength meter, and measuring the force when the particles are broken, which is then used as the particle strength value. Alternatively, the particle strength can be obtained by randomly selecting about 20 active material particles, measuring their particle strength, and then taking the average value.
[0087] Methods for preparing positive electrode active materials
[0088] A method for preparing a positive electrode active material according to some embodiments includes: preparing core particles comprising a lithium transition metal composite compound; preparing an average size (D) of less than or equal to about 2.5 μm. 50 Plate-shaped carbon materials; and dry mixing (dry mixing) of core particles and plate-shaped carbon materials to obtain positive electrode active materials.
[0089] In a method for preparing a positive electrode active material according to some embodiments, a carbon coating layer comprising graphene having a layered structure of 50 layers or less can be formed on the surface of the core particles using plate-like carbon materials. Therefore, the particle strength and surface lubricity of the positive electrode active material can be improved while minimizing manufacturing costs. Furthermore, the method for preparing the positive electrode active material provides a positive electrode active material that ensures adhesion strength and conductivity to the electrode plate even when small amounts of binder and conductive materials are used during the fabrication of the positive electrode. Additionally, as the amount of binder used in the fabrication of the positive electrode decreases, the amount of positive electrode active material can increase, allowing the rechargeable lithium battery including the positive electrode active material to exhibit high capacity and high energy density characteristics.
[0090] The following describes in detail a method for preparing a positive electrode active material according to some embodiments.
[0091] Prepare core particles
[0092] Core particles comprising lithium transition metal complexes can be prepared. These core particles may possess the properties described above in the section on positive electrode active materials.
[0093] Prepare plate-shaped carbon materials
[0094] It can prepare materials with an average size (D) of less than or equal to about 2.5 μm. 50 Plate-shaped carbon materials. Specific properties of plate-shaped carbon materials, such as average size and I... D / I G The value can be the same as that in the plate-shaped carbon materials and positive electrode active materials described above.
[0095] During the preparation process, an average size (D) of approximately 3 μm to approximately 25 μm can be obtained. 50 The raw materials are pulverized to prepare materials with an average size (D) of less than or equal to about 2.5 μm. 50 A plate-shaped carbon material. Raw materials may include graphene, graphite, or a combination thereof. The average size (D) of the raw material... 50The size of the raw material can be less than or equal to about 20 μm, less than or equal to about 18 μm, less than or equal to about 15 μm, less than or equal to about 12 μm, less than or equal to about 10 μm, greater than or equal to about 3.5 μm, greater than or equal to about 4 μm, or greater than or equal to about 4.5 μm. Here, the average size of the raw material can be measured from SEM images. The average size of the raw material (D...) 50 Particle size can be measured by a particle size analyzer and refers to the size of particles that have a cumulative volume of 50% in the particle size distribution. Furthermore, particle size here can mean the length of the longest axis in a plane perpendicular to the thickness direction in a plate shape.
[0096] The raw material may have a Raman spectrum of greater than or equal to about 0.01 and less than about 0.15, for example about 0.02 to about 0.14, about 0.08 to about 0.14, or about 0.1 to about 0.14 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G ).
[0097] The raw materials can be pulverized, for example, using a grinding process. The grinding process can be a method known to those skilled in the art, and equipment such as ball mills, bead mills, spray mills, pin mills, roller mills, mixing (hybrid) mills, colloid mills, or air classifiers (ACMs) can be used.
[0098] The raw materials can be pulverized using ball milling. Ball milling can be performed using zirconia beads with a size of about 1 mm to about 25 mm at a speed of about 200 rpm to about 5,000 rpm for about 5 minutes to about 4 hours. The size of the zirconia beads used to pulverize the raw materials can be about 1.2 mm to about 23 mm, about 1.3 mm to about 21 mm, or about 1.5 mm to about 20 mm. The pulverization of the raw materials can be carried out at speeds of about 250 rpm to about 4,500 rpm, about 300 rpm to about 4,000 rpm, about 400 rpm to about 3,000 rpm, or about 600 rpm to about 2,000 rpm. The pulverization of the raw materials can be carried out for about 5 minutes to about 3 hours or about 30 minutes to about 3 hours. When the bead size, stirring speed, or stirring time are each within these ranges, the particle size of the plate-like carbon material can be controlled to the desired level.
[0099] Obtain the positive electrode active material
[0100] Core particles and plate-shaped carbon materials are mixed to prepare the positive electrode active material. In this process, crystalline carbon derived from the plate-shaped carbon material coats the surface of the core particles, thereby forming a carbon coating layer on the surface of the core particles comprising graphene with a layered structure of 50 layers or less. Because the carbon coating layer is formed on the surface of the core particles with a thin and uniform thickness, the particle strength and surface lubricity of the positive electrode active material can be improved in this process. Furthermore, even when a small amount of binder is used during the formation of the positive electrode, the adhesion strength and conductivity to the electrode plate can be ensured. In addition, as the amount of binder used to manufacture the positive electrode decreases, the amount of positive electrode active material can be increased, allowing the rechargeable lithium battery to exhibit high capacity and high energy density characteristics. The carbon coating layer formed in this process can be the same as the carbon coating layer in the positive electrode active material described above, and its detailed description is omitted.
[0101] Based on a total of 100% by weight of core particles and plate-shaped carbon material, the plate-shaped carbon material can be mixed in amounts from about 0.05% by weight to about 5.0% by weight, for example from about 0.1% by weight to about 5.0% by weight, from about 0.2% by weight to about 5.0% by weight, from about 0.2% by weight to about 3.0% by weight, from about 0.2% by weight to about 2.5% by weight, from about 0.2% by weight to about 2.0% by weight, from about 0.2% by weight to about 1.0% by weight, or from about 0.2% by weight to about 0.8% by weight. When the amount of plate-shaped carbon material mixed in these ranges, the particle strength and lubricity of the positive electrode active material can be improved. Even if the amount of plate-shaped carbon material is less than about 1% by weight, it can still effectively coat the surface of the core particles to thereby increase the electrical conductivity of the positive electrode active material, increase lubricity, and increase the density of the positive electrode.
[0102] The process can be performed at speeds of approximately 500 rpm to approximately 6,000 rpm, for example, approximately 600 rpm to approximately 5,500 rpm, approximately 700 rpm to approximately 5,000 rpm, or approximately 800 rpm to approximately 4,000 rpm. When the conditions are within these ranges, the particle strength and surface lubricity of the positive electrode active material can be improved.
[0103] This process can be performed by mixing core particles and plate-like carbon material and applying shear force. In this case, a carbon coating layer comprising graphene exhibiting a dense crystalline structure with a layered structure can be formed, while crystalline carbon derived from the plate-like carbon material is provided in a two-dimensional plane on the surface of the core particles. This process can be performed using equipment for applying shear force, such as equipment with internal blades. However, this disclosure is not limited to such examples.
[0104] This process involves mixing core particles and plate-shaped carbon materials using a mixer, such as a Nobilta mixer (Hosokawa Micron BV). The core particles and plate-shaped carbon materials can be mixed at approximately 1,000 s. -1 From approximately 9,000 s -1 The shear rate and blade rotation speed are mixed at or less than about 20 m / s. In a further embodiment, the core particles and plate-shaped carbon material can be mixed at about 1,500 s. -1 From approximately 8,800 s -1 Approximately 2,000 s -1 From approximately 8,800 s -1 Or approximately 2,500 s -1 From approximately 8,500 s -1 The shear rates are mixed. When the shear rates are within these ranges, a carbon coating layer can be effectively formed on the surface of the core particles without damaging the core particles.
[0105] The rotational speed of the blades within the device applying shear force can be less than or equal to about 18 m / s, less than or equal to about 15 m / s, less than or equal to about 10 m / s, greater than or equal to about 3 m / s, greater than or equal to about 4 m / s, or greater than or equal to about 5 m / s. When the rotational speed of the blades is within these ranges, a carbon coating layer can be effectively formed on the surface of the core particle without damaging the core particle.
[0106] Core particles and plate-shaped carbon materials can be dry-mixed. This reduces manufacturing costs and improves particle strength and surface lubrication of the positive electrode active material because the carbon coating is thin and uniformly formed. Here, "dry" means a state in which there is no intentional contact with a solvent, such as a process solvent, or a state in which a solvent is not intentionally included. Dry mixing can be performed using methods known to those skilled in the art, such as dry mixers, homogenizers, or Henschel mixers.
[0107] positive electrode
[0108] According to some embodiments, the positive electrode includes a current collector. A positive electrode active material layer is disposed on the current collector and includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types of positive electrode active materials. In such cases, the aforementioned positive electrode active material may be referred to as a first positive electrode active material, and positive electrode active materials of a different type from the aforementioned positive electrode active material may be referred to as a second positive electrode active material, a third positive electrode active material, etc.
[0109] The configuration of the positive electrode according to some embodiments is described in detail below.
[0110] Second positive electrode active material
[0111] In addition to the first positive electrode active material described above, the positive electrode active material layer may include a second positive electrode active material, which comprises a lithium transition metal composite oxide. The average particle size (D) of the first positive electrode active material... 50 The particle size can be from about 6 μm to about 25 μm, and the average particle size (D) of the second positive electrode active material can be from about 6 μm to about 25 μm. 50 The particle size can range from approximately 1 μm to approximately 8 μm. The first positive electrode active material with a relatively large average particle size can be represented as large particles, and the second positive electrode active material with a relatively small average particle size can be represented as small particles. Because the positive electrode active material layer includes both large and small particles, it can have maximized capacity and energy density, as well as long cycle life characteristics.
[0112] Typically, positive electrode active materials comprising lithium nickel-based composite oxides have been proposed to maximize capacity, energy density, and long cycle life characteristics by mixing large and small particles. However, positive electrodes comprising both large and small particles can experience problems such as cracking or surface damage in the large particles during compression processes. Consequently, capacity degradation can be accelerated with repeated charging and discharging of the battery, leading to reduced cycle life characteristics.
[0113] According to some embodiments, the first positive electrode active material (i.e., large particles) of the positive electrode can have high particle strength and provide good lubrication to the particle surface because it provides a carbon coating layer on the surface of the core particle formed from secondary particles. Therefore, breakage in the large particles (which would otherwise occur during compression of the positive electrode) can be mitigated, and the compression process can be performed at higher pressures. Additionally, a positive electrode comprising both large and small particles can have reduced porosity in the electrode plate and improved density in the positive electrode active material layer.
[0114] Because the lithium transition metal complex oxide of the second positive electrode active material can be the same as that of the first positive electrode active material described above, further detailed descriptions will be omitted. For example, the type of lithium transition metal complex oxide in the second positive electrode active material can be the same as or different from the type of lithium transition metal complex oxide in the first positive electrode active material.
[0115] The second positive electrode active material can be secondary particles, single particles, or a combination thereof formed by the aggregation of primary particles. Since the form of secondary particles is as described above, further detailed description will be omitted.
[0116] When the second positive electrode active material is in the form of a single particle, it can have various shapes, such as polyhedral, spherical, ellipsoidal, plate-shaped, rod-shaped, or irregular. Here, the single particle exists independently without grain boundaries within it, consisting of a single particle, and can be a single particle, a monolithic (monomer-like) structure, an integral structure, or non-agglomerated particles, wherein the particles do not aggregate but exist as an independent phase in terms of morphology. A single particle can be represented as a single crystal.
[0117] The average particle size (D) of the active material of the second positive electrode 50 The particle size can be from about 1 μm to about 8 μm, and can be, for example, from about 1 μm to about 7.5 μm, from about 1 μm to about 7 μm, or from about 1 μm to about 6 μm. When the average particle size (D) of the second positive electrode active material... 50 Within these ranges, capacity, energy density, and long cycle life characteristics can be maximized. Here, the average particle size (D) of the second positive electrode active material... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from the SEM image of the active material of the second positive electrode, measuring the particle size (diameter, major axis or major axis length) to obtain the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0118] The second positive electrode active material may include particles comprising a lithium transition metal composite oxide and a carbon coating layer on the surface of the particles. In this case, the particle strength and surface lubricity of the second positive electrode active material can be improved. The carbon coating layer of the second positive electrode active material may include graphene having a layered structure of 50 layers or less, and the graphene may be derived from plate-like carbon materials. Because these details are the same as those described above, further detailed descriptions will be omitted.
[0119] Based on a total of 100% by weight of first and second positive electrode active materials, the positive electrode active material layer may include about 20% to about 95% by weight, for example about 30% to about 90% by weight, about 45% to about 85% by weight, or about 60% to about 80% by weight of the first positive electrode active material, and may include about 5% to about 80% by weight, for example about 10% to about 70% by weight, about 15% to about 55% by weight, or about 20% to about 40% by weight of the second positive electrode active material. When the amounts of the first and second positive electrode active materials are within these ranges, the capacity and mixing density of the positive electrode can be improved, and the energy density of the rechargeable lithium battery can be further improved.
[0120] current collector
[0121] There are no limitations on the current collector, as long as it is conductive and does not cause undesirable chemical changes to the positive electrode and the rechargeable lithium battery including the positive electrode. For example, the current collector may include thin films of aluminum (Al), stainless steel (SUS), indium (In), magnesium (Mg), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or combinations thereof, and may include, for example, aluminum thin films.
[0122] Current collectors can take many shapes and forms, such as plates, thin sheets, films, sheets, foils, meshes, porous bodies, foams, or nonwoven materials. In some examples, current collectors may include microscopic irregularities on their surface, which can improve the adhesion strength to the positive electrode active material.
[0123] The thickness of the current collector can be from about 1 μm to about 20 μm, for example from about 5 μm to about 15 μm or from about 7 μm to about 15 μm.
[0124] In addition to the positive electrode active material mentioned above, the positive electrode active material layer may further include a binder, a conductive material, or a combination thereof.
[0125] adhesive
[0126] The binder is used to adhere the positive electrode active material particles to each other and to adhere the positive electrode active material to the current collector. The binder may include, for example, one or more of the following: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide (including polymers containing ethylene oxide), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, and nylon. However, this disclosure is not limited to these examples.
[0127] In the positive electrode active material layer, based on a total of 100% by weight of the positive electrode active material layer, a binder may be included in an amount of about 0.1% by weight to about 5% by weight, for example, about 0.5% by weight to about 4% by weight, or about 1% by weight to about 3% by weight. For example, based on a total of 100% by weight of the positive electrode active material layer, a binder may be included in an amount of about 0.1% by weight to about 1% by weight, for example, less than about 1.0% by weight, or less than or equal to about 0.9% by weight. Because the positive electrode active material layer includes the aforementioned first and second positive electrode active materials, it can exhibit excellent electronic conductivity, low resistance, and high positive electrode density even if it does not contain a separate binder or contains a very small amount of binder.
[0128] conductive materials
[0129] Conductive materials are used to provide conductivity to electrodes and can be any material that does not cause undesirable chemical changes and is an electronic conductor in a battery. For example, conductive materials may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metal-based materials including metal powders or fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0130] In the positive electrode active material layer, based on a total of 100% by weight of the positive electrode active material layer, conductive material may be included in an amount from about 0.05% by weight to about 5% by weight, for example, from about 0.5% by weight to about 4% by weight, or from about 1% by weight to about 3% by weight. For example, based on a total of 100% by weight of the positive electrode active material layer, conductive material may be included in an amount from about 0.05% by weight to about 1% by weight, for example, less than about 1.0% by weight, less than or equal to about 0.8% by weight, less than or equal to about 0.7% by weight, or less than or equal to about 0.5% by weight. Because the positive electrode active material layer includes the aforementioned first positive electrode active material, even if the positive electrode active material layer does not include a separate conductive material or includes a very small amount of conductive material, it can still exhibit excellent electronic conductivity and have low resistance and high positive electrode density.
[0131] The density of the positive electrode active material layer can be greater than or equal to about 3.3 g / cc, and can be, for example, about 3.3 g / cc to about 5.0 g / cc, about 3.5 g / cc to about 4.8 g / cc, about 3.8 g / cc to about 4.5 g / cc, or about 3.82 g / cc to about 4.5 g / cc. When the density of the positive electrode active material layer is within these ranges, the energy density of the rechargeable lithium battery can be improved. For example, because the positive electrode active material included in the positive electrode active material layer has high particle strength and lubricity, the compression process can be performed at higher pressures during the formation of the positive electrode. In addition, because the surface lubricity of the positive electrode active material is high, the compression efficiency of the positive electrode can be improved through the sliding effect. Furthermore, because the compression process can be performed at higher pressures, the porosity of the electrode plates in the positive electrode active material layer can be reduced, and the density of the positive electrode active material layer can be further improved. Here, the density of the positive electrode active material layer means the weight-to-volume ratio of the positive electrode active material layer in the compressed positive electrode. The density of the positive electrode active material layer can be obtained by measuring the cross-sectional area, thickness, and weight of the positive electrode active material layer excluding the positive electrode current collector, calculating the volume by multiplying the cross-sectional area by the thickness, and dividing the weight by the volume.
[0132] The adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 0.5 gf / mm. The resistivity of the positive electrode active material layer can be less than or equal to about 40 Ω·cm. For example, the adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 1.1 gf / mm, greater than or equal to about 1.5 gf / mm, greater than or equal to about 2.0 gf / mm, or greater than or equal to about 2.5 gf / mm, less than or equal to about 30 gf / mm, less than or equal to about 28 gf / mm, less than or equal to about 25 gf / mm, or less than or equal to about 23 gf / mm. The resistivity of the positive electrode active material layer can be less than or equal to about 35 Ω·cm, less than or equal to about 30 Ω·cm, less than or equal to about 25 Ω·cm, less than or equal to about 20 Ω·cm, greater than or equal to about 0.5 Ω·cm, greater than or equal to about 1.0 Ω·cm, greater than or equal to about 3.0 Ω·cm, greater than or equal to about 5.0 Ω·cm, or greater than or equal to about 5.5 Ω·cm. Because the positive electrode active material layer includes the aforementioned positive electrode active materials, it exhibits excellent electronic conductivity and low resistance even if it does not contain a separate conductive material or contains only a very small amount of conductive material. Even if it contains only a very small amount of binder, the positive electrode active material layer can have high electrode plate adhesion strength.
[0133] The thickness of the positive electrode active material layer can be from about 40 μm to about 300 μm, for example from about 50 μm to about 200 μm, or from about 80 μm to about 150 μm. When the thickness of the positive electrode active material layer is within these ranges, high-capacity and high-energy-density batteries can be achieved. The thickness of the positive electrode active material layer can be measured using SEM images of the positive electrode cross-section. However, this disclosure is not limited thereto, and the thickness of the positive electrode active material layer can be measured, for example, by TEM, TOF-SIMS, XPS, or EDS analysis.
[0134] The porosity of the positive electrode can be less than or equal to about 30%, less than or equal to about 25%, less than or equal to about 20% and greater than or equal to about 1%, greater than or equal to about 5%, or greater than or equal to about 7%. When the porosity of the positive electrode is within these ranges, the capacity and energy density of the positive electrode can be improved. Here, the porosity of the positive electrode means the ratio of the pores present within the positive electrode to the total volume of the positive electrode. Porosity can be measured, for example, by mercury porosimetry (mercury porosimetry).
[0135] Rechargeable lithium batteries
[0136] A rechargeable lithium battery according to some embodiments includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a current collector and a layer of positive electrode active material on the current collector, wherein the layer of positive electrode active material includes the aforementioned positive electrode active material. The rechargeable lithium battery may be a lithium-ion battery using a liquid electrolyte, or an all-solid-state rechargeable battery or a semi-solid-state rechargeable battery using a solid electrolyte.
[0137] Depending on their shape, rechargeable lithium batteries can be cylindrical, prismatic, pouch-shaped, coin-shaped, etc. Figures 1 to 4 To illustrate a schematic diagram of a rechargeable lithium battery according to some embodiments, wherein Figure 1 It is a cylindrical battery. Figure 2 It is a prismatic battery, and Figure 3 and 4 It is a pouch-shaped battery.
[0138] Reference Figures 1 to 4 The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 between a positive electrode 10 and a negative electrode 20, and the electrode assembly 40 is housed within the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution (not shown). The rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50, such as... Figure 1 As shown. Additionally, in Figure 2 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and 4 As shown, the rechargeable lithium battery 100 includes electrode terminals 70, namely, a positive electrode terminal 71 and a negative electrode terminal 72, which form an electrical path for leading the current generated in the electrode assembly 40 to the outside of the battery.
[0139] According to some embodiments, rechargeable lithium batteries may be rechargeable at high voltage or suitable for driving at high voltage. For example, the charging voltage of a rechargeable lithium battery may be greater than or equal to about 4.45 V, about 4.45 V to about 4.7 V, about 4.45 V to about 4.6 V, or about 4.45 V to about 4.55 V, etc. By using the positive electrode active material according to embodiments of the present disclosure, even when the battery is charged at high voltage, the amount of gas generated in the rechargeable lithium battery can be significantly reduced, and the battery has high capacity and long cycle life characteristics.
[0140] negative electrode
[0141] The negative electrode may include a current collector and a negative electrode active material layer on the current collector. The negative electrode active material layer includes a negative electrode active material, and may further include a binder, a conductive material, or a combination thereof.
[0142] Negative electrode active material
[0143] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0144] The material capable of reversibly intercalating / deintercalating lithium ions may be or include a carbon-based negative electrode active material such as crystalline carbon, amorphous carbon, or a combination thereof. The crystalline carbon may be irregular, flake-like, scaly, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonized product, calcined coke, and the like.
[0145] As the alloy of lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.
[0146] The material capable of doping and dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may be silicon, a silicon-carbon composite, SiO x (0<x≤2), a Si-Q alloy, or a combination thereof. In the formula Si-Q, Q is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element (excluding Si), a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or a combination thereof, and for example Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO₂, a Sn-based alloy, or a combination thereof.
[0147] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle diameter (D 50) may be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles having amorphous carbon coated on the surface of the silicon particles. For example, the silicon-carbon composite may include secondary particles (core) formed by aggregated silicon primary particles and an amorphous carbon coating layer (shell) on the surface of the secondary particles. Amorphous carbon may also be present between the silicon primary particles, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0148] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core including crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon or hard carbon, mesophase pitch carbonized product, calcined coke, and the like.
[0149] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be about 10 wt% to about 50 wt% and the amount of amorphous carbon may be about 50 wt% to about 90 wt%. When the silicon-carbon composite includes silicon, amorphous carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be about 10 wt% to about 50 wt%, the amount of crystalline carbon may be about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be about 20 wt% to about 40 wt%.
[0150] The thickness of the amorphous carbon coating layer may be about 5 nm to about 100 nm. The average particle diameter (D of the silicon particles (primary particles) 50 ) may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as elemental silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented as SiO x (0<x≤2). The atomic content ratio of Si:O indicating the oxidation degree may be about 99:1 to about 33:67.
[0151] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material is used in combination with the carbon-based negative electrode active material, the weight ratio of the Si-based negative electrode active material or Sn-based negative electrode active material to the carbon-based negative electrode active material may be about 1:99 to about 90:10.
[0152] The negative electrode active material may be included in an amount of about 80 wt% to about 99 wt%, for example, about 85 wt% to about 99 wt% or about 90 wt% to about 99 wt%, based on 100 wt% of the total negative electrode active material layer.
[0153] adhesive
[0154] The binder is used to adhere the active material particles of the negative electrode to each other, and also to adhere the active material of the negative electrode to the current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0155] Non-aqueous adhesives may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.
[0156] Waterborne adhesives may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxygenated alcohol, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or combinations thereof.
[0157] When an aqueous binder is used as the negative electrode binder, it may further include a cellulose-based compound capable of imparting viscosity. As a cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts may be mixed and used. The alkali metal may be Na, K, or Li.
[0158] Dry adhesives can be fibrous polymer materials. Examples of dry adhesives include, for instance, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), PVDF-hexafluoropropylene copolymer, polyethylene oxide (PEO), or combinations thereof.
[0159] Based on 100% by weight of the total negative electrode active material layer, the binder may be included in an amount of about 0.5% by weight to about 5% by weight, for example, about 0.5% by weight to about 4% by weight or about 1% by weight to about 3% by weight.
[0160] conductive materials
[0161] This includes conductive materials to provide electrode conductivity, and any electrically conductive material that does not cause undesirable chemical changes can be used. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0162] Based on 100% by weight of the total negative electrode active material layer, conductive material may be included in an amount of about 0.5% by weight to about 5% by weight, for example, about 0.5% by weight to about 4% by weight or about 1% by weight to about 3% by weight.
[0163] current collector
[0164] There are no particular restrictions on the negative electrode current collector, as long as it does not cause undesirable chemical changes in the negative electrode and the rechargeable lithium battery including the negative electrode. As an example, the negative electrode current collector may be copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0165] The negative electrode current collector can take various shapes and forms, such as plates, thin sheets, films, sheets, foils, meshes, porous bodies, foams, or nonwoven materials. In some examples, the negative electrode current collector may include microscopic irregularities on its surface, which can improve the adhesion strength to the negative electrode active material.
[0166] The thickness of the negative electrode current collector can be from about 1 μm to about 20 μm, for example from about 5 μm to about 15 μm or from about 7 μm to about 10 μm.
[0167] electrolytes
[0168] The electrolyte used in rechargeable lithium batteries may be an electrolyte solution, which may include non-aqueous organic solvents and lithium salts.
[0169] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of a battery. Non-aqueous organic solvents may be carbonate (carbonate-based) solvents, ester (ester-based) solvents, ether (ether-based) solvents, ketone (ketone-based) solvents, alcohol (alcohol-based) solvents, aprotic solvents, or combinations thereof.
[0170] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), etc.
[0171] Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc.
[0172] Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc.
[0173] Ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group, and may include double bonds, aromatic rings, or ether groups, etc.); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane, etc.
[0174] Non-aqueous organic solvents can be used alone or in mixtures of two or more types. When two or more types are used in mixtures, the mixing ratio can be adjusted according to the desired battery performance, as is widely known to those skilled in the art.
[0175] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used together. Cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.
[0176] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. For example, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0177] The electrolyte solution may further include vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve battery cycle life.
[0178] Examples of ethylene carbonate compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0179] Lithium salts dissolved in organic solvents supply lithium ions in the battery, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts include one or more selected from the following: LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).
[0180] The concentration of lithium salt can range from about 0.1 M to about 2.0 M. When the concentration of lithium salt is within this range, the electrolyte solution has suitable ionic conductivity and viscosity. This results in excellent performance and efficient movement of lithium ions.
[0181] diaphragm
[0182] Depending on the type of rechargeable lithium battery, the rechargeable lithium battery may further include a separator located between the positive and negative electrodes. For example, the separator may include a multilayer membrane of polyethylene, polypropylene, polyvinylidene fluoride, or two or more layers thereof, and a hybrid multilayer membrane such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.
[0183] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.
[0184] The porous substrate may be a polymer film formed from any polymer selected from: polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, and Teflon® (polytetrafluoroethylene), or copolymers or mixtures of two or more thereof. The porous substrate may include glass fiber, or may include a composite film of polymer and glass fiber.
[0185] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0186] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit derived from (meth)acrylamide, the second structural unit including at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylaminosulfonic acid or a salt thereof.
[0187] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, Ga2O3, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. However, this disclosure is not limited to these examples. The average particle size (D) of the inorganic particles... 50The average particle size (D) of the inorganic particles can be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm, or from about 100 nm to about 700 nm. Here, the average particle size (D) of the inorganic particles is... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from the scanning electron microscope image of inorganic particles, measuring their particle size (diameter, major axis or major axis length) to obtain the particle size distribution, and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0188] Organic and inorganic materials can be mixed in a single coating. In other embodiments, a coating comprising organic materials and a coating comprising inorganic materials can be stacked. The thickness of the coating can be from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm, or from about 1 μm to about 5 μm.
[0189] The rechargeable lithium-ion batteries described in the examples can be used in automobiles, mobile phones, or various types of electronic devices. However, this disclosure is not limited to these examples.
[0190] The following describes embodiments and comparative examples of the present invention. These embodiments are for illustrative purposes only, and the present disclosure is not limited to these embodiments.
[0191] Example 1
[0192] (1) Preparation of positive electrode active material
[0193] Flake-shaped graphite (G5 (Qingdao Luowei New Materials); average particle size (D) 50 ZrO2 beads with an average particle size of 5.0 μm were mixed with 10 times the weight of flake graphite and 2 mm particle size. The flake graphite and beads were then milled at 1,000 rpm for 1 hour to prepare a ZrO2 bead with an average particle size of 0.2 μm (D0). 50 ) graphite microparticles.
[0194] In preparing LiNi in the form of secondary particles formed by the aggregation of multiple primary particles. 0.91 Co 0.05 Al 0.01 The core particles of O2 (average particle size (D)) 50 After approximately 14 μm, 99.8% by weight of the core particles and 0.2% by weight of the graphite microparticles were placed in a dry mixer. After adjusting the mixing speed to 3,000 rpm, the core particles and graphite microparticles were dry-mixed for 10 minutes to obtain the positive electrode active material.
[0195] (2) Positive electrode
[0196] The prepared positive electrode active material forms the first positive electrode active material, and has an average particle size (D) of approximately 2 μm. 50 LiNi in single-particle form 0.91 Co 0.05 Al 0.01 The second positive electrode active material is composed of O2. The first and second positive electrode active materials were mixed at a weight ratio of 70:30. Then, 97.7% by weight of the mixture, 1.0% by weight of carbon nanotubes and carbon black (in a weight ratio of 7:3) as conductive materials, and 1.3% by weight of polyvinylidene fluoride as a binder were dispersed in N-methylpyrrolidone (NMP) solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry was coated onto a 12 μm thick aluminum substrate (current collector) and dried to form a positive electrode active material layer. The resulting material was then compressed at a pressure of 25 MPa to fabricate the positive electrode. SEM analysis of the compressed positive electrode revealed that the positive electrode active material layer had a thickness of approximately 50 μm.
[0197] (3) Rechargeable lithium battery cells
[0198] The above-prepared positive electrode and lithium metal pair (negative electrode) are used to manufacture a rechargeable lithium battery cell having a polyethylene-polypropylene multilayer separator between the positive and negative electrodes. The rechargeable lithium battery cell is manufactured by injecting an electrolyte solution containing 1.3 M LiPF6 lithium salt in a solvent comprising ethylene carbonate, propylene carbonate, and propyl propionate mixed in a volume ratio of 10:15:75.
[0199] Example 2
[0200] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: in the preparation of the positive electrode active material, the positive electrode active material was prepared by mixing 99.5% by weight of core particles and 0.5% by weight of graphite microparticles.
[0201] Example 3
[0202] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: in the preparation of the positive electrode active material, the positive electrode active material was prepared by mixing 99.0% by weight of core particles and 1.0% by weight of graphite microparticles.
[0203] Example 4
[0204] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: in the preparation of the positive electrode active material, the positive electrode active material was prepared by mixing 98.0% by weight of core particles and 2.0% by weight of graphite microparticles.
[0205] Comparative Example 1
[0206] Core particles were prepared as the positive electrode active material for the preparation of the positive electrode active material in Example 1. The prepared positive electrode active material was used to fabricate the positive electrode and the rechargeable lithium battery cell in the same manner as in Example 1.
[0207] Comparative Example 2
[0208] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: in the preparation of the positive electrode active material, 0.2% by weight of flake graphite (G5 (Qingdao Luowei New Materials)) for preparing graphite microparticles was mixed; the average particle size (D) 50 The positive electrode active material was prepared by using 5.0 μm core particles and 99.8% by weight.
[0209] Comparative Example 3
[0210] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: in the preparation of the positive electrode active material, carbon black (Super P of Imerys SA) was mixed with the core particles instead of graphite microparticles.
[0211] Comparative Example 4
[0212] The positive electrode active material, positive electrode, and rechargeable lithium battery cell were prepared in the same manner as in Example 1, except that: in the preparation of the positive electrode active material, carbon nanotubes were mixed with the core particles instead of graphite particles.
[0213] Evaluation Example 1: Electron Microscopy Image Analysis of Positive Electrode Active Material
[0214] SEM images of the positive electrode active material of Example 1 are shown below. Figure 5 In the figure, the SEM image of Comparative Example 3 is shown. Figure 6 In the middle, and the SEM image of Comparative Example 4 is shown in Figure 7 middle.
[0215] refer to Figure 5The positive electrode active material of Example 1 has a layered carbon coating layer formed on the surface of the core particle, and the carbon coating layer is also formed on the surface of the primary particles of the core particle. The carbon coating layer is very thin, uniform in thickness, and surrounds the surface of the core particle.
[0216] At the same time, refer to Figure 6 and 7 Comparative Examples 3 and 4, which have carbon coatings derived from carbon black and carbon nanotubes, are unevenly aggregated on the surface of the core particles or partially aggregated on a portion of the surface of the core particles.
[0217] Furthermore, the cross-sections of the positive electrode active materials of Examples 1 to 4 were observed using transmission electron microscopy (TEM). The results confirmed that a coating layer comprising a layered graphene structure having two or more layers was formed on each of the positive electrode active materials.
[0218] Evaluation Example 2: SEM Image Analysis of the Positive Electrode
[0219] SEM images of the positive electrodes of Examples 1 and 2 and Comparative Examples 1 to 4 were captured and are shown below. Figures 8 to 13 middle.
[0220] Figure 8 The embodiments shown are 1 and 2. Figure 9 Example 2 shown exhibits minimal breakage in the active material particles due to the compression process. In particular, Example 2 shows less breakage than Example 1. In other words, it can be seen that the particle strength of the positive electrode active material is maximized by controlling the amount of carbon coating.
[0221] Meanwhile, compared with Examples 1 and 2, Figure 10 Comparative Example 1 shown exhibits a significant amount of breakage of the active material particles. In other words, since the positive electrode active materials of Examples 1 and 2 include a carbon coating layer that improves particle strength, less breakage occurs due to the compression process.
[0222] Reference Figure 11 Compared to Examples 1 and 2, the active material particles of Comparative Example 2, which have a carbon coating layer derived from a plate-shaped carbon material with a large average particle size, exhibited a significant amount of breakage. In other words, it can be seen that by controlling the average particle size of the plate-shaped carbon material, the particle strength of the positive electrode active material is maximized.
[0223] Compared with Examples 1 and 2, Figure 12 Comparative Example 3 and shown Figure 13Comparative Example 4 shown (both having carbon coatings derived from carbon black (a carbon material with a zero-dimensional structure) and carbon nanotubes (a carbon material with a one-dimensional structure)) exhibits significant particle breakage of the active material. Therefore, it can be seen that by controlling the type of carbon material, the particle strength of the positive electrode active material can be maximized.
[0224] Evaluation Example 3: Analysis of the physical properties of the positive electrode active material
[0225] The particle strength of the positive electrode active materials of the examples and comparative examples was analyzed, and the results are shown in Table 1 below. The specific evaluation method is as follows.
[0226] The active material particles were placed on a plate and then compressed by increasing the compressive force using a micro-compression testing machine (MCT-W500 from Shimadzu Corp.). Here, the force at which the particles were broken was measured, and the particle strength of the active material particles was obtained by averaging the particle strength of a total of 20 particles.
[0227] Evaluation Example 4: Analysis of the physical properties of the positive electrode
[0228] The density of the positive electrode active material layer of the positive electrode in the analytical examples and comparative examples is shown in Table 1 below. The specific evaluation method is as follows.
[0229] The cross-sectional area, thickness, and weight of each positive electrode active material layer, excluding the positive electrode current collector, were measured. The cross-sectional area was then multiplied by the thickness to calculate the volume, and the weight was divided by the volume to calculate the density of each positive electrode active material layer.
[0230] Table 1
[0231]
[0232] Referring to Table 1, Examples 1 to 4 have particle strengths ranging from 165 MPa to 185 MPa. Therefore, it is confirmed that Examples 1 to 4 have high particle strengths.
[0233] Examples 1 to 4 have densities ranging from 3.87 g / cc to 3.93 g / cc. In other words, in Examples 1 to 4, where the positive electrode active material has high particle strength, the mixing density of the electrode plates increases.
[0234] On the other hand, in Comparative Example 1, where there is no carbon coating layer on the surface of the core particles and therefore the particle strength is lower than that of Examples 1 to 4, the density of the positive electrode active material layer is reduced. In Comparative Example 2, which has a plate-like carbon material with a larger average particle size than that of Example 1, the particle strength of the active material and the density of the positive electrode active material layer are lower than those of Example 1. Comparative Examples 3 and 4, where the carbon coating layer is derived from carbon black and carbon nanotubes, have lower particle strength than that of Example 1, and therefore, the density of the positive electrode active material layer is lower.
[0235] Evaluation Example 5: Performance Analysis of a Rechargeable Lithium-ion Battery Cell
[0236] The initial discharge capacity and capacity retention (cycle life characteristics) of the rechargeable lithium battery cells in the analysis examples are shown in Table 2 below. The evaluation method is as follows.
[0237] (1) Initial discharge capacity
[0238] At 25°C, rechargeable lithium-ion battery cells were charged under constant current (0.2 C) and constant voltage (4.3 V, 0.05 C cutoff), paused for 10 minutes, and then discharged to 3.0 V under constant current (0.2 C) for initial charging and discharging. The initial discharge capacity of the battery cells was measured.
[0239] (2) Capacity retention
[0240] After initial charging and discharging, the battery cells were charged and discharged 50 times at 0.33 C / 1 C at 25°C to measure the discharge capacity at the 50th cycle. The ratio of the discharge capacity at the 50th cycle to the discharge capacity at the 1st cycle was calculated and expressed as the capacity retention rate (cycle life characteristic).
[0241] Table 2
[0242]
[0243] Referring to Table 2, Examples 1 to 4 exhibited initial discharge capacities of 213.1 mAh / g to 213.7 mAh / g and capacity retention rates of 94.8% to 95.9%. In particular, Examples 1 to 3 demonstrated higher capacity and higher capacity retention than Example 4. In other words, it can be seen that capacity and cycle life characteristics improved when the amount of carbon coating was controlled. On the other hand, Comparative Examples 1 to 4 exhibited reduced capacity retention and deteriorated cycle life characteristics compared to Examples 1 to 4.
[0244] While this disclosure has been described in conjunction with exemplary embodiments now considered practical, it will be understood that this disclosure is not limited to the disclosed embodiments. Rather, this disclosure includes various modifications and equivalent arrangements.
[0245] <Description of reference numerals in the attached figures>
[0246] 100: Rechargeable lithium battery; 10: Positive electrode
[0247] 11: Positive electrode lead connector 12: Positive electrode terminal
[0248] 20: Negative electrode 21: Negative electrode lead connector
[0249] 22: Negative electrode terminal; 30: Diaphragm
[0250] 40: Electrode assembly; 50: Housing
[0251] 60: Sealing component; 70: Electrode terminal piece
[0252] 71: Positive electrode connector; 72: Negative electrode connector
Claims
1. Positive electrode active material, including: Core particles, which include lithium transition metal composite oxides and are in the form of secondary particles that are agglomerated as primary particles; and A carbon coating layer on the surface of the core particles; The positive electrode active material has a particle strength of 160 MPa or greater.
2. The positive electrode active material according to claim 1, wherein the particle strength of the positive electrode active material is 160 MPa to 190 MPa.
3. The positive electrode active material according to claim 1, wherein the carbon coating layer comprises graphene having a layered structure of 50 layers or less.
4. The positive electrode active material according to claim 3, wherein the graphene is derived from plate-shaped carbon materials.
5. The positive electrode active material according to claim 4, wherein the plate-shaped carbon material comprises graphene, graphite, or a combination thereof.
6. The positive electrode active material according to claim 4, wherein the average size D of the plate-like carbon material particles is... 50 Less than or equal to 2.5 μm.
7. The positive electrode active material according to claim 4, wherein the average size D of the plate-like carbon material particles is... 50 The range is from 50 nm to 900 nm.
8. The positive electrode active material according to claim 4, wherein the thickness of the plate-like carbon material is 5 nm to 100 nm.
9. The positive electrode active material according to claim 1, wherein the carbon coating layer is in the form of a continuous film or an island.
10. The positive electrode active material according to claim 1, wherein the carbon coating layer has a Raman spectrum of 0.15 to 0.50 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .
11. The positive electrode active material according to claim 1, wherein the carbon coating layer is included in an amount from 0.1% to 5.0% by weight based on 100% by weight of the positive electrode active material.
12. The positive electrode active material according to claim 1, wherein the carbon coating layer is included in an amount of 0.2% to 1.0% by weight based on 100% by weight of the positive electrode active material.
13. The positive electrode active material according to claim 1, wherein the thickness of the carbon coating layer is from 2 nm to 500 nm.
14. The positive electrode active material according to claim 1, wherein the lithium transition metal composite oxide of the core particle is a lithium nickel-based composite oxide represented by: Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 where 0.9≤a1≤1.2, 0.3≤x1<1, 0<y1≤0.7, 0≤z1≤0.7, 0.9≤x1+y1+z1≤1.1, and 0≤b1≤0.1, M 1 and M 2 are each independently one or more of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, Y, W and Zr, and X is one or more of F, P and S.
15. The positive electrode active material according to claim 1, wherein the average particle size D of the secondary particles is... 50 The primary particles are 6 μm to 25 μm in size, and the average particle size D of the primary particles is... 50 The range is from 10 nm to 1 μm.
16. Positive electrode, including: Current collector, and A positive electrode active material layer disposed on the current collector and comprising the positive electrode active material according to any one of claims 1 to 15 The positive electrode active material according to any one of claims 1 to 15 is the first positive electrode active material.
17. The positive electrode of claim 16, wherein the positive electrode active material layer further comprises a second positive electrode active material, the second positive electrode active material comprising a lithium transition metal composite oxide, and Wherein the average particle size D of the first positive electrode active material 50 The particle size is 6 μm to 25 μm, and the average particle size D of the second positive electrode active material is... 50 The range is from 1 μm to 8 μm.
18. The positive electrode according to claim 16, wherein the second positive electrode active material is a lithium-nickel based composite oxide represented by: Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 wherein 0.9≤a1≤1.2, 0.3≤x1<1, 0<y1≤0.7, 0≤z1≤0.7, 0.9≤x1+y1+z1≤1.1, and 0≤b1≤0.1, M 1 and M 2 are each independently one or more selected from the group consisting of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, Y, W and Zr, and X is one or more selected from the group consisting of F, P and S.
19. The positive electrode according to claim 16, wherein the density of the positive electrode active material layer is from 3.3 g / cc to 5.0 g / cc.
20. A rechargeable lithium battery, comprising: The positive electrode according to any one of claims 16 to 19; negative electrode; and Electrolytes.